Effect of Computer Animations on Students’ Understanding of Neural Conduction via Annotated Drawings and Graphical Representations - Priyamvada,; Deepshikha, (JOURNAL OF INDIAN EDUCATION, 2021)
The purpose of this study is to show how use of computer animations in teaching is an effective way of revealing the misconceptions of students about the basic concepts in Biology. Two sample schools—multipurpose urban model and residential rural school—were selected for the study. Students of Class XI of age group 16–18 years (N = 80) participated in this study. A twostage experiment in the form of drawing sessions—before and after formal technical teaching was conducted following an open-ended interview to explore students’ basic understanding and cause of misconceptions about neural conduction. During each drawing session, the children were asked to draw the annotated diagrams and graphical representations of the processes taught on the basis of their own observation and understanding. The drawings and graphs were analysed and categorised based on five levels of the drawing criteria given by Köse (2008). The connections they draw and explanations they give to their drawings depict that they have several misconceptions regarding the concepts of ‘Neural Control and Coordination’.